Trecuseră doi când m-am apucat de jucat - Pălici, Bogdan; Budeş, Matei; Gal, Simona (Romania : Vira Films, 2009)
The brief existence of a sequence of folk dances generally named Maruntele, at the beginning of the 20th century, raises the interest of a group of young researchers who start a real exercise in social archeology in order to gather memories, parts of songs and steps from the vanished dance. A meditation on traditions and cultural heritage in the 21st century.
Verzio Film Festival Submission
Verzio Film Festival Submission